(untitled) (IPS Journal of Public Health, 2023)
Cancer causes significant physical and emotional impairments in its sufferers. Not only patients, cancer may indirectly affect many of whom are the primary caregivers. This work investigated the caregiver burdens of cancer patients in Rivers State University Teaching Hospital (RSUTH). The study hypotheses were developed and a population size of 100 respondents was determined using Taro Yamane’s formula. A questionnaire was designed and validated while data was collected from primary and secondary sources. Data collected were analyzed using a frequency table, percentage and mean score analysis while the nonparametric statistical test (Chi-square) was used to test the formulated hypothesis using SPSS. The results obtained from the three hypotheses which include the test: (i) that there was no level of care burdens among informal caregivers of cancer patients, (ii) that there was no quality of life of informal caregivers of cancer patients, and (iii) that there was no correlation between burdens of care and quality of life of family caregivers of cancer patients revealed that the majority of the respondents were of the opinion that there was a level of care burdens among informal caregivers of cancer patients. Secondly, there was a quality of life of informal caregivers of cancer patients and thirdly, there was a correlation between burdens of care and quality of life of family caregivers of cancer patients in RSUTH.